2018
DOI: 10.1111/jscm.12180
|View full text |Cite
|
Sign up to set email alerts
|

Trustworthiness Change and Relationship Continuity after Contract Breach in Financial Supply Chains

Abstract: The management of financial flows in the supply chain is an integral part of effective supply chain management and is an emerging research area. A breach in the relationships between firms and financial providers may not only affect the financial health of the focal firms, but also disrupt the financial stability of their supply chains. Building on life‐cycle theory, this research examines the critical role of trustworthiness in the financial supply chain relationships in the event of a contract breach. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 123 publications
(179 reference statements)
2
18
0
Order By: Relevance
“…Ta et al. () examine the critical role of trustworthiness in the financial supply chain relationships in the event of a contract breach. However, in this paper, we focus more on the optimal decisions in operations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ta et al. () examine the critical role of trustworthiness in the financial supply chain relationships in the event of a contract breach. However, in this paper, we focus more on the optimal decisions in operations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wagner et al () further showed that suppliers’ reputations for honesty, fairness, and concern for buyers fostered relationship continuity and future collaboration intent from the buyer’s perspective. The supplier attribute of trustworthiness, which reflects the buyer’s belief that the supplier is reliable and will adhere to their obligations in the relationship (Inkpen, ), is not static but varies along the relationship life cycle in buyer–supplier relationships (Ta et al, ). Since buyer–supplier relationships are often characterized by interpersonal interactions of individual agents, scholars have highlighted that supplier attributes might also involve amicable attitudes toward suppliers based on positive emotions and social benefits to purchasing managers (Gligor & Autry, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this study, we maintain that the meaning and the effects of supplier attributes are contingent on the relational context of buyer–supplier relationships. This is because (1) several supplier attributes emerge in the course of repeated interactions (e.g., Ta, Esper, Ford, & Garcia‐Dastuge, ; Wagner, Coley, & Lindemann, ), (2) varying and negative (dark‐side) effects of supplier attributes could only be explained in the relational context of buyer–supplier relationships (e.g., Anderson & Jap, ; Narayanan & Narasimhan, ), and (3) supplier attributes are not always fully objective but can result from the perception of the individuals (i.e., purchasing managers) who are carrying out supply chain management practices (Kaufmann, Meschnig, & Reimann, ). With that backdrop, this study has two main objectives: To revisit the concept of the supplier attribute.…”
Section: Introductionmentioning
confidence: 99%
“…Not only inter-firm collaboration, but intra-firm collaboration as well, i.e., between departments of the organisation, is found to be essential for SCF (Wandfluh et al 2016;Caniato et al 2016). Trust is an integral part of supply chain financing, and several researchers have stressed that trust is essential (Randall and Farris 2009;Wuttke et al 2013b;Liebl et al 2016;Martin 2017;Blackman and Holland 2006;Karyani et al 2015;Ta et al 2018). Martin (2017) stated that trust exists when there is honesty and benevolence.…”
Section: Factors Influencing the Acceptance Of Supply Chain Financementioning
confidence: 99%
“…Martin (2017) stated that trust exists when there is honesty and benevolence. The parties involved in the supply chain need to maintain trustworthiness, and Ta et al (2018) mentioned that changes in the trustworthiness can play a crucial role in maintaining a relationship. It is important for the SC partners to maintain openness (Randall and Farris 2009) and fairness ).…”
Section: Factors Influencing the Acceptance Of Supply Chain Financementioning
confidence: 99%